Study of Bamboo Ethnobotany by the Local Community Residing around Mount Galunggung in Tasikmalaya Regency (Indonesia) - Yanty, Desty; Hernawati, Diana; Putra, Rinaldi Rizal (Journal of Tropical Ethnobiology, 2024)
This research aims to determine the ethnobotany of bamboo plants by the community around Mount Galunggung, Tasikmalaya Regency, as a source of biology learning. The research method used was descriptive qualitative. Sampling was carried out using purposive sampling with the population of Mandalagiri Village, precisely in the Paniis and Sukatani Villages. The data collection method was by interviews with primary and secondary data sources. Data analysis was carried out using data reduction techniques, data presentation, and conclusions, and a qualitative SUV (Species Use Velues) analysis was carried out to determine the use value of bamboo species. The results of the research show that the community around Mount Galunggung utilizes six species of bamboo, namely Chinese bamboo (Bambusa multiplex), yellow bamboo (Bambusa vulgaris), apus bamboo (Gigantochloa apus), black bamboo (Gigantochloa atroviolaceae), ater bamboo (Gigantochloa atter), and bamboo gombong (Gigantochloa verticillata) in everyday life. This use is done in arts, crafts, agriculture, furniture, food, medicine, construction, collections, ornamental plants, beliefs, and ecology. Gigantochloa apus has the most essential value, with a score of 0.42, meaning this species has the most benefits.